Bezpodstawne wzbogacenie w prawie bułgarskim: [Groundless enrichment in the Bulgarian law] (Studia Prawnicze / The Legal Studies, 1983)
The article is a monograph on the institution of groundless enrichment in the Bulgarian law and doctrine. It is based on the literature and judicial decisions.The above mentioned institution is regulated by art. 55-59 of the law on obligations and contracts of 1950. Moreover, settlement of accounts in virtue of fulfilment of a null and void contract, was regulated as a separate institution (art. 34 of the law on obligations and contracts) as well as enrichment gained vilely (art. 36 of the law on property and executory provisions).The article analyses: the genesis of the institution, its normative sources, monistic approach (undue prestation was not separated from groundless enrichment, although structural and theoretical elements of such a separation have been noticed in the literature), premises of establishing an obligation to return profits (impoverishment and enrichment, mutual relation between them, lack of appropriate legal grounds - this premise is not 'unanimously understood in the Bulgarian literature), content and scope of an obligation to return (Bulgarian Taw breaks with the requirement of real enrichment and requires the return of gained profits), the problem of relation of claim under groundless enrichment with other claims (in this respect claim under undue prestation may compete with other claims, whereas a general norm providing for an obligation to return profits which were gained by other reasons than undue prestation is of a subsidiary character). The article ends with considerations on vile enrichment (Bulgarian Jaw provides for the forfeiture of the property on behalf of the state.